التحكيم في المنازعات البحرية : دراسة تحليلية في القانون الليي في ضوء الاتفاقيات الدولية - شريف، سالمة فرج (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2012)
The purpose of this thesis is to provide an analytical study of the arbitration in maritime disputes in Libyan Law, and the international conventions. Maritime arbitration is the system of resolutions of disputes in maritime matters outside the court. The parties which involve in dispute do not prefer to solve their problem before the courts. They choose an arbitration because of the features and advantages of the arbitration itself. This research aims to reform many dilemmas in the Libyan law because of lacking of the research and references on the arbitration especially in maritime disputes. Furthermore, there are no enough experts on arbitrations and particularly in maritime disputes according to what has been viewed. Since there is no specific provisions in neither the Libyan law nor the international conventions cover the maritime arbitration, the researcher has applied the general rules of arbitration, which is included in the Libyan civil law, commercial law and the international conventions, in the maritime disputes, taking into consideration the nature of these disputes. This study follows the comparative, a critical and an analyzing approach and the field research by interview the experts in arbitration. The research of the arbitration of the maritime disputes concentrates in two main axes: the Arbitration Agreement and the Arbitration Court. Thus, the important findings of this research are: the will of the parties is the basis in maritime arbitration. They choose the arbitration as a resolution of dispute instead of the competent court. In addition, the maritime arbitration is not different from the other types of arbitration in nature. However, the difference could be found in the nature of the maritime disputes. And its interrelation with commercial matters. Furthermore, the lacking of Libyan law and the international conventions in maritime arbitration, where are regulate the arbitration in general without considering of the specific nature of maritime disputes.